2006
DOI: 10.1073/pnas.0601824103
|View full text |Cite
|
Sign up to set email alerts
|

Common attributes of native-state structures of proteins, disordered proteins, and amyloid

Abstract: We show that a framework derived from the common character of globular proteins can be used to understand the design of protein sequences, the behavior of intrinsically unstructured proteins, and the formation of amyloid fibrils in a unified manner. Our studies provide compelling support for the idea that protein native-state structures, the structures adopted by intrinsically unstructured proteins on binding as well as those of amyloid aggregates, all reside in a physical state of matter in which the free ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
36
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 45 publications
5
36
0
Order By: Relevance
“…Such symmetry and geometry consideration leads to a presculpted free energy landscape 30 with marginally compact protein-like ground states and low energy minima 33,34 . Interestingly, the model also shows a strong tendency of multiple chains to form amyloid-like aggregates 32,35 , similar to that found in higher resolution models 24,36,37 . Extensive simulations have been carried out by Auer and coworkers [38][39][40][41] to study the fibril formation of 12-mer homo-peptides using the tube model with a slightly different constraint on self-avoidance, showing useful insights on the nucleation mechanism 38,39 of fibril formation and on the equilibrium conditions between the fibrillar aggregates and the peptide solution 40,41 .…”
Section: Introductionsupporting
confidence: 50%
See 2 more Smart Citations
“…Such symmetry and geometry consideration leads to a presculpted free energy landscape 30 with marginally compact protein-like ground states and low energy minima 33,34 . Interestingly, the model also shows a strong tendency of multiple chains to form amyloid-like aggregates 32,35 , similar to that found in higher resolution models 24,36,37 . Extensive simulations have been carried out by Auer and coworkers [38][39][40][41] to study the fibril formation of 12-mer homo-peptides using the tube model with a slightly different constraint on self-avoidance, showing useful insights on the nucleation mechanism 38,39 of fibril formation and on the equilibrium conditions between the fibrillar aggregates and the peptide solution 40,41 .…”
Section: Introductionsupporting
confidence: 50%
“…Previous study of the tube model 35 has shown that hydrophobic-polar sequence can select protein's secondary and tertiary structures. In particular, the HPPH and HPPPH patterns have been identified as strong α-formers, whereas the HPH pattern is a β-former.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17,18 Exact primarystructure symmetry within repeated domains provides opportunities for domain mismatches producing misfolded forms with near-native Gibbs energy, and low sequence identities could have a crucial and general role in safeguarding proteins against misfolding and aggregation; 19 furthermore, primary-structure symmetry is one feature of amyloid-type aggregates. 20 Thus, while symmetric protein architecture offers attractive advantages for de novo design, there is a need for novel approaches to successfully identify foldable peptide building blocks from those that might otherwise misfold or aggregate.…”
Section: Introductionmentioning
confidence: 99%
“…The algorithm is based on an energy function for specific ␤-aggregation, which was derived from a large group of non-redundant high resolution x-ray structures of globular proteins (44). The assumption that information regarding the structure of amyloid fibrils can be deduced by studying the structures of globular proteins rests on the well established observation (45,46) that the aggregation mediated by nonnative ␤-pairings is a possible mode that polypeptide chains may adopt against insufficient folding stability. By assuming that the globular protein data base represents a system in thermodynamic equilibrium at a single temperature, which is supposed to be roughly constant for all proteins in the data bank, it then follows that the propensities p ab P(A) of finding a given residue pair ab in the ensemble, with a and b facing each other in neighboring parallel (P) or antiparallel (A) ␤-strands, are given by p ab P(A) ϭ exp(ϪE ab P(A) ), where ϪE ab P(A) are effective adimensional energies, and both a and b run over the 20 different amino acids (47).…”
Section: Methodsmentioning
confidence: 99%